Effects of antiarrhythmic drugs on hERG gating in human-induced pluripotent stem cell-derived cardiomyocytes from a patient with short QT syndrome type 1 - Huang, Mengying; Liao, Zhenxing; Li, Xin; Yang, Zhen; Fan, Xuehui; Li, Yingrui; Zhao, Zhihan; Lang, Siegfried; Cyganek, Lukas; Zhou, Xiao-Bo; Akın, Ibrahim; Borggrefe, Martin; et al. (Frontiers in pharmacology, 2021)
Aims The short QT syndrome type 1 (SQT1) is linked to hERG channel mutations (e. g. N588K). Drug effects on hERG channel gating kinetics in SQT1-cells have not been investigated. Methods This study used hiPSC-CMs of a healthy donor and a SQT1-patient carrying the N588K mutation and patch clamp to examine the drug effects on hERG channel gating kinetics. Results Ajmaline, amiodarone, ivabradine, flecainide, quinidine, mexiletine and ranolazine inhibited the hERG channel current (IKr) less strongly in hiPSC-CMs from the SQTS1-patient (SQT1-hiPSC-CMs) comparing with cells from the healthy donor (donor-hiPSC-CMs). Quinidine and mexiletine reduced, but ajmaline, amiodarone, ivabradine and ranolazine increased the time to peak of IKr similarly in SQT1-hiPSC-CMs and donor-hiPSC-CMs. Although regarding the shift of activation and inactivation curves, tested drugs showed differential effects in donor- and SQT1-hiPSC-CMs, quinidine, ajmaline, ivabradine and mexiletine but not amiodarone, flecainide and ranolazine reduced the window current in SQT1-hiPSC-CMs. Quinidine, ajmaline, ivabradine and mexiletine differentially changed the time constant of recovery from inactivation, but all of them increased the time constant of deactivation in SQT1-hiPSC-CMs. Conclusion The window current-reducing and deactivation-slowing effects may be important for the antiarrhythmic effect of ajmaline, ivabradine, quinidine and mexiletine in SQT1-cells. This information may be helpful for selecting drugs for treating SQT1-patients with hERG channel mutation.
Gesehen am 29.05.2021 ; 07.10.2021